2011
DOI: 10.1007/s13187-011-0271-6
|View full text |Cite
|
Sign up to set email alerts
|

“The Promise of Community-Based Advocacy and Education Efforts for Increasing Cancer Clinical Trials Accrual”

Abstract: Only 3% of cancer patients participate in cancer clinical trials (CCTs). A number of barriers to participation, particularly for minority groups, can be addressed through community-focused education and advocacy efforts. Working with community partnerships, a pilot program sought to change knowledge, attitudes, and role behaviors among community leaders, primary care providers (PCPs), and clinical researchers about CCTs, to increase patient awareness of and participation in CCTs. A mixed method evaluation util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 23 publications
(23 reference statements)
0
45
1
Order By: Relevance
“…A wide and representative sample of participants in clinical research is essential to ensure adequate generalization of the findings to the population at large [57,70]. Informed persons and research participants could assist in enforcement of research standards (ethical and methodological) and increase the quality of data generated.…”
Section: Methodologicalmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide and representative sample of participants in clinical research is essential to ensure adequate generalization of the findings to the population at large [57,70]. Informed persons and research participants could assist in enforcement of research standards (ethical and methodological) and increase the quality of data generated.…”
Section: Methodologicalmentioning
confidence: 99%
“…This makes research more costly and less powerful in detecting meaningful therapeutic effects, and it delays the arrival of new treatments to those who need them [57,65,[71][72][73].…”
Section: Methodologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,5 A study conducted by the Education Network to Advance Cancer Clinical Trials found that PCPs who attended an education program about clinical trials had a statistically significant increase in knowledge about the training content and an increase in "positive attitudes about the role of a PCP for CCT referrals." 5 The training focused on discussions PCPs could have with patients and their families about clinical trials and the role of clinical trials as an element of quality care. 5 When holding meetings at the office of a referring physician, it is important to involve nurses and other ancillary staff at the practice.…”
Section: Build Relationshipsmentioning
confidence: 99%
“…5 The training focused on discussions PCPs could have with patients and their families about clinical trials and the role of clinical trials as an element of quality care. 5 When holding meetings at the office of a referring physician, it is important to involve nurses and other ancillary staff at the practice. These individuals can be very influential and often serve as "research champions."…”
Section: Build Relationshipsmentioning
confidence: 99%